Sensibilité du chômage et caractéristiques de l’offre et de la demande sur le marché du travail - de Broucker, Patrice (L'Actualité économique, 1981)
ABSTRACTIn this article, we look at the impact of both supply and demand of labour on the determination of the unemployment rate. The analysis is conducted with annual data by 12 demographic groups over the period 1956-1978. All the data prior to 1976 from the Labour Force Survey were adjusted to the definition of the new Survey. A few differences in the reaction of demographic group unemployment rate are noticeable: (a) in general, male unemployment rates react much more to demand side evolution while female rates are more influenced by movements in the supply of labour; (b) some groups clearly exhibit "discouraged worker" behaviour when facing adverse economic conditions, (namely youths, women aged 25 to 34 and older men); (c) due to a lower sensitivity to economic conditions of many of their jobs, adult women present a fairly stable situation of employment, so their growing unemployment rates are the result of higher competition stemming from an increasing desire to participate in the work world; (d) together these findings have some implications for government policies; more specifically, they emphasize the limitations of demand policy and point to the need for selective measures and a diversification of job opportunities for women.